2016
DOI: 10.1111/jfd.12530
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical changes and tissue distribution of Enterocytozoon hepatopenaei (EHP) in naturally and experimentally EHP‐infected whiteleg shrimp, Litopenaeus vannamei (Boone, 1931), in India

Abstract: Stunted growth in pond-reared Litopenaeus vannamei was observed in different farms located in Tamil Nadu and Andhra Pradesh, India. No mortality was associated with stunted growth. PCR assay on these samples revealed the presence of Enterocytozoon hepatopenaei (EHP) in stunted shrimp. Tissue distribution of EHP in naturally and experimentally infected shrimp was studied by PCR and histology. Histological examination revealed the presence of EHP in hepatopancreas and gut, but not in other organs. The PCR assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 24 publications
3
27
0
Order By: Relevance
“…The introduction of exotic species has the risk of disease outbreaks caused by the pathogens which are not reported previously in India. Recently, the occurrence of Enterocytozoon hepatopenaei and IMNV has been reported after the introduction of L. vannamei to Indian aquaculture system (Rajendran et al, ; Sahul Hameed et al, ; Santhoshkumar et al, ). Behera et al () reported for the first time the occurrence of TiLV in Nile tilapia farms in India.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of exotic species has the risk of disease outbreaks caused by the pathogens which are not reported previously in India. Recently, the occurrence of Enterocytozoon hepatopenaei and IMNV has been reported after the introduction of L. vannamei to Indian aquaculture system (Rajendran et al, ; Sahul Hameed et al, ; Santhoshkumar et al, ). Behera et al () reported for the first time the occurrence of TiLV in Nile tilapia farms in India.…”
Section: Discussionmentioning
confidence: 99%
“…ALT and AST are two important indexes, which can reflect the function of liver. Under normal conditions, the activities of transaminases in serum remain low, unless the tissues is damaged or lesions (Nazeri, Farhangi, & Modarres, ; Santhoshkumar et al, ). When the pathological changes occur, the necrosis of tissue cells leads to the release of a large number of transaminases into blood, which would cause the increase of the contents of ALT and AST (Kalhoro et al, ; Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The tissue samples were also screened for WSSV, IHHNV and EHP by PCR using virus‐ and EHP‐specific primers after extracting DNA from the samples based on published protocols (Lo et al., ; Yoganandhan, Sathish, Murugan, Narayanan, & Sahul Hameed, ; Tang et al. ; Santhoshkumar et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…A surveillance programme supported by National Fisheries Development Board of ICAR is being carried out to monitor shrimp culture systems throughout the country for emerging diseases in shrimp and fish. As a result of this programme for the past 3 years, the occurrence of Enterocytozoon hepatopenaei in pond‐reared L. vannamei (Rajendran et al., ; Santhoshkumar et al., ) and cyprinid herpesvirus‐2 in goldfish (Sahoo et al., ) has been reported. In our surveillance, the occurrence of infectious myonecrosis virus (IMNV) in pond‐reared L. vannamei has been reported for the first time in India.…”
Section: Introductionmentioning
confidence: 99%